Modulating the platelet-mediated innate foreign body response to affect in situ vascular tissue engineering outcomes - Mackenzie E. Turner; Jingru Che; Joseph T. Leland; Delaney J. Villarreal; Sahana Rajesh; Sugath Suravarapu; Kan N. Hor; Matthew G. Wiet; Bryce A. Kerlin; Tai Yi; Cameron A. Best; James W. Reinhardt; et al. (npj Regenerative Medicine)
Abstract The success of implanted tissue-engineered vascular grafts (TEVGs) relies on the coordinated inflammation and wound healing processes that simultaneously degrade the scaffold and guide the formation of a neovessel. Dysregulated responses can lead to aberrant remodeling (e.g., stenosis), impacting the long-term outcome and functionality of the TEVG. We developed a TEVG that, despite demonstrating growth capacity in the clinic, exhibited an unexpectedly high incidence of stenosis, or narrowing of the graft lumen. This study identified platelet-mediated immune signaling via the lysosomal trafficking regulator (Lyst) as a key driver of stenosis. Lyst mutations significantly impaired platelet dense granule exocytosis yet preserved alpha granule secretion and adhesion to the biomaterial. Uncontrolled platelet aggregation, potentiated by dense granule signaling, results in the formation of a mural thrombus that remodels into occlusive neotissue. Importantly, inhibiting sustained platelet aggregation using the P2Y12 antagonist, prasugrel, is a successful strategy for optimizing neotissue formation and improving overall TEVG performance.